POLITENESS IN TEACHER- STUDENT INTERACTIONS: APOLOGY ACTION BASED-CASES - FAQE, CHIAYE KHORSHEED; LUTFI, ABBAS FADHIL (Journal of Duhok University, 2023)
The current research paper aims to explore apology actions of politeness in teacher-student interactions in academic settings. In the current study, the researchers attempted to make use of the discursive approach to politeness as a post-modern view of politeness. Eelen (2001), Mills (2003), and Watts (2005) were launched noticeable criticism against Brown and Levinson and proposed the discursive approach. The present study has utilized a qualitative research method. It enabled researchers to collect detailed data on participants’ experiences, which could be analyzed using interpretive methods to identify key themes and patterns. The results show that there is politeness in teacher-student interactions, in particular apology actions which serve as a particularly meaningful manifestation of politeness within teacher-student interactions. Moreover, various aspects related to politeness in teacher-student interactions, such as the cultural influences on politeness norms, and the role of power dynamics in shaping politeness behaviors should be taken into consideration